A new species of Chrysochlamys (Clusiaceae, Clusioideae, Clusieae) from the Cordillera Azul National Park, Loreto, Peru - Rojas Gonzales, Rocio Del Pilar (2023)
Chrysochlamys montieliae, a new species of the Clusiaceae family, Clusioideae subfamily, Clusieae tribe, from the Cordillera Azul National Park, Department of Loreto, is described and illustrated. Following the IUCN criteria, we propose to categorize it as Data Deficient (DD), since it is only known from the type locality. In addition, their relationships with related species are discussed.